Faktor-Faktor yang Mempengaruhi Kejadian Tuberkulosis pada Umur 15 Tahun ke Atas di Indonesia - Lamria Pangaribuan; Kristina Kristina; Dian Perwitasari; Teti Tejayanti; Dina Bisara Lolong (Buletin Penelitian Sistem Kesehatan, 2020)
Today, Pulmonary Tuberculosis still remains a notable health concern in Indonesia. Pulmonary Tuberculosis (called TB) is a disease of ancientness who determined by numerous factors. These factors are relating to host, including age, sex, race, socioeconomic, lifestyle, marital status, work, heredity, nutrition and immunity. This study aimed to ﬁ nd out on inﬂ uence factors pulmonary tuberculosis occurrence of 15 years old or above in Indonesia, according to the Tuberculosis Prevalence Survey Data Year 2013-2014. A Cross-Sectional study design. The Number of Samples aged 15 years or above was 67,944. We had performed analysis from secondary data of Tuberculosis Prevalence Survey Year 2013-2014 using Univariate, Bivariate, and Multivariate Logistic Regression analysis. Multivariate analysis showed that participants who had been: diagnosed with TB by a health professional [OR = 6.06 (95% CI; 4.69–7.83)], aged 35-54 years [OR = 1.22 (CI95%; 0 , 96 - 1.5)], aged 55 years + [OR = 1.73 (CI95%; 1.32-2.27)], male [OR = 2.07 (CI95%; 1.60-2 , 69)], Urban areas [OR = 1.48 (CI95%; 1.21-1.80)], Eastern Indonesia Region [OR = 1.59 (CI95%; 1.26-2.02)], Sumatera Region [OR = 1.68 (CI95%; 1.32-2.12)], education level < Junior High School [OR = 1.48 (CI95%; 1.19-1.83)], diagnosed with DM by a physician [OR = 1.44 (95% CI; 0.92-2.25)], lived with TB patient [OR = 1.84 (CI95%; 1.27-2.65)], smoking [OR = 1.25 (CI95%; 098-1.60)]. Furthermore, the ﬁ nal model shows that all independent variables are factors inﬂ uencing TB cases that occurred in Indonesia (p <0.05). These variables are a group of age, sex, regional classiﬁ cation, areas, education level, had been diagnosed with DM by a physician, had been diagnosed with TB by a health professional, and had been lived with TB sufferer. The most dominant factor inﬂ uencing TB occurrence of 15 years or above had been diagnosed with TB. Thus, it concluded that the participant had a risk of 6.06 times the occurrence of TB compared to the participant who had never been diagnosed with TB by a health professional. Abstrak Saat ini tuberkulosis masih menjadi masalah utama kesehatan di Indonesia. Penyakit TB dipengaruhi oleh beberapa faktor pejamu. Adapun faktor yang berkaitan dengan pejamu antara lain usia, jenis kelamin, ras, sosial ekonomi, kebiasaan hidup, status perkawinan, pekerjaan, keturunan, nutrisi, dan imunitas. Studi ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi kejadian Tuberkulosis pada umur 15 tahun ke atas di Indonesia berdasarkan data SPTB 2013-2014. Disain studi potong lintang. Jumlah sampel yang berumur 15 tahun ke atas adalah 67.944. Analisis data dengan univariat, bivariate, dan multivariat regresi logistik. Analisis Multivariat menunjukkan bahwa partisipan yang pernah di diagnosis TB oleh tenaga kesehatan [OR= 6,06 (CI 95%; 4,69–7,83)], umur 35-54 tahun [OR=1,22 (CI95%;0,96 – 1,5)], umur 55 tahun+ [OR= 1,73 (CI95%; 1,32-2,27)], laki-laki [OR= 2,07 (CI95%; 1,60-2,69)], Perkotaan [OR=1,48 (CI95%; 1,21-1,80)], Kawasan Timur Indonesia [OR= 1,59 (CI95%; 1,26-2,02)], Kawasan Sumatera [OR=1,68 (CI95%; 1,32-2,12)], Pendidikan < SMP [OR=1,48 (CI95%; 1,19-1,83)], pernah di diagnosis DM oleh dokter [OR=1,44 (CI95%; 0,92-2,25)]. Pernah tinggal dengan penderita TB [OR=1,84 (CI95%; 1,27-2,65)], Merokok [OR=1,25 (CI95%; 098-1,60)]. Pada model akhir terlihat bahwa seluruh variabel independen merupakan faktor-faktor yang mempengaruhi kejadian TB di Indonesia (p<0,05) adalah kelompok umur, jenis kelamin, klasiﬁ kasi daerah, kawasan, pendidikan, pernah di diagnosis DM oleh dokter, pernah di diagnosis TB oleh tenaga kesehatan, dan pernah tinggal dengan penderita TB. Faktor yang paling dominan mempengaruhi terjadinya TB pada usia 15 tahun ke atas adalah pernah di diagnosa TB oleh tenaga kesehatan. Partisipan yang pernah di diagnosa TB oleh tenaga kesehatan berisiko 6,06 kali untuk terjadinya TB dibandingkan orang yang belum pernah di diagnosa TB oleh tenaga kesehatan.